PROMOTER REGION rs1800629 TNFα POLYMORPHISM AND ITS INFLUENCE ON TUMOR NECROSIS FACTOR ALPHA CONCENTRATION IN BLOOD OF HEALTHY INDIVIDUALS AND PATIENTS WITH ERYSIPELAS - A. S. Emelyanov; A. N. Emelyanova; B. S. Pushkarev; Yu. A. Vitkovsky (Медицинская иммунология, 2018)
Erysipelas is an actual problem of health care. It is characterized by consistently high morbidity, excepted tendency to recur, reduced the life quality and took important place in the structure of temporary disability. The changes of immunological reactivity, depended on genetic characteristics of the individual were established to play important role in the pathogenesis of erysipelas. The prediction of the course of erysipelas is unresolved problem yet. The genetic features of the organism, such as the genetic polymorphisms of some cytokines, involved on the prediction of the course of erysipelas. Investigations of TNFα genes demonstrated that their transcriptions increased and productions enhanced. Aim was to study the influence of polymorphism of TNFα gene promoter rs1800629 on the concentration of TNFα in the blood of healthy individuals and patients with erysipelas in primary and recurrent course. The study was performed at 104 patients with erysipelas (54 patients with primary erysipelas and 50 patients with recurrent course) and 94 healthy residents. Gene polymorphism of TNFα rs1800629 was detected by PCR method. Measurement of the concentration of TNFα was performed by immunoassay analysis. Homo- and heterozygous SNP of the TNFα rs1800629 gene were conformed to Hardy–Weinberg equilibrium (p > 0.05). Minor allele A was found to be registered in erysipelas patient less frequently by 2.9 times than in healthy individuals. The patients who carried homozygous G/G were observed in 88.7% of cases. At that heterozygous G/A were registered in any case. In other case, among the patients, no cases of the carriage of the mutant genotypes A/A were detected. Thus, allele G and genotypes G/G of promoter gene of TNFα rs1800629 predisposed to erysipelas. Heterozygous G/A of promoter gene of TNFα rs1800629 increased the risk of erysipelas. G-allele carrier led to decrease of TNFα concentration homozygous G/G patients.